2013
DOI: 10.1186/1472-6882-13-129
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of selected Malaysian honey

Abstract: BackgroundAntibacterial activity of honey is mainly dependent on a combination of its peroxide activity and non-peroxide components. This study aims to investigate antibacterial activity of five varieties of Malaysian honey (three monofloral; acacia, gelam and pineapple, and two polyfloral; kelulut and tualang) against Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Pseudomonas aeruginosa.MethodsMinimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) were performed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
123
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 24 publications
11
123
0
2
Order By: Relevance
“…Tualang honey was reported to be effective for wound healing and wound burn management (Nasir et al, 2010) and the effects of different types of honey on tensile strength evaluation of burn wound tissue healing were evaluated by Rozaini et al (2004). The types of phenolic acidsin Malaysian honey were suggested to be responsible for the antibacterial properties (Aljadi and Yusoff, 2003) while other local Malaysian honey showed antimicrobial activity on some human pathogens (Tumin et al, 2005;Hassanain et al, 2010;Zainol et al, 2013). Propolis of Malaysian honey inhibited the growth of Staphylococcus aureus and Escherichia coli as reported by Rahman et al (2010).…”
Section: Ajasmentioning
confidence: 60%
See 1 more Smart Citation
“…Tualang honey was reported to be effective for wound healing and wound burn management (Nasir et al, 2010) and the effects of different types of honey on tensile strength evaluation of burn wound tissue healing were evaluated by Rozaini et al (2004). The types of phenolic acidsin Malaysian honey were suggested to be responsible for the antibacterial properties (Aljadi and Yusoff, 2003) while other local Malaysian honey showed antimicrobial activity on some human pathogens (Tumin et al, 2005;Hassanain et al, 2010;Zainol et al, 2013). Propolis of Malaysian honey inhibited the growth of Staphylococcus aureus and Escherichia coli as reported by Rahman et al (2010).…”
Section: Ajasmentioning
confidence: 60%
“…The highest inhibitory was shown by H020 from Libya against S. aureus (27.50±0.70 mm), S. Typhimurium (19.00±1.41 mm), B. subtilis (19.50±00.70 mm) and P. aeruginosa (18.50±2.12 mm) and from H032 from Malaysia against E. coli (17.00±0.00 mm). Zainol et al (2013) tested the antibacterial activity of several Malaysian honeys including Acacia and Tualang and one New Zealand honey (Manuka 18+) using well method against S. aureus, E. coli, P.aeruginosa and B. cereus; the results varied from 7.59 to 27.35 mm diameter, the highest inhibitory zone was obtained from Manuka honey against S. aureus (19.81 mm) and E. coli (14.04 mm), comparable inhibitory activity from Tualang honey against P. aeruginosa (16.22 mm) and B. cereus (27.35 mm), while Acacia honey showed the lowest result compared to other samples. In the present study the ability of Al-Seder honey and Acacia honey to kill target bacteria using well method was higher than what observed by Tualang, Acacia and Manuka 18+ as reported by Zainol et al (2013) against all MAR target bacteria.…”
Section: Ajasmentioning
confidence: 99%
“…Therefore, it can be stored for long period of time (at least 2 years) without any additional treatment or supplementation with preservatives. When honey is diluted to certain extent, its antibacterial activity is shifted from osmotic-and pH-dependent to peroxide-dependent mechanism of action based on the generation of H 2 O 2 [26]. This scenario takes place when honey is used for treatment of infections, e.g.…”
Section: Basic Information and Mechanisms Of Antimicrobial Activitymentioning
confidence: 99%
“…Previous study showed that stingless bee honey can act as anti-inflammatory (Borsato et al, 2014), anticancer (Kustiawan et al, 2014;Yazan et al, 2016), antimicrobial (Miorin et al, 2003;Demera et al, 2004;Garedew et al, 2004;Temaru et al, 2007;Kimoto-Nira and Amano, 2008;Chanchao et al, 2009;Boorn et al, 2010;Rodríguez et al, 2012;Ilechie et al, 2012;Andualem, 2013;Ewnetu et al, 2013;Mercês et al, 2013;Queiroz et al, 2013;Zainol et al, 2013;Nobre da Cruz et al, 2014;Massaro et al, 2014;Zamora et al, 2014;Medeiros et al, 2016;De Sousa et al, 2016; and possessed antioxidant properties (Duarte et al, 2012;Almeida da Silva et al, 2013;De Sousa et al, 2016). However, the beneficial of stingless bee honey has been abandoned in modern medicine due to the paucity of systematic scientific studies for supporting its medical properties (Pe´rez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%